IMPLEMENTASI REHABILITASI SOSIAL GELANDANGAN DAN PENGEMIS MELALUI PROGRAM BIMBINGAN KETERAMPILAN KERJA DI PANTI SOSIAL BINA KARYA “PANGUDI LUHUR” BEKASI - Rachmawati, Mita; Rahayu, Ety (Jurnal Pembangunan Manusia, 2020)
The number of homeless and beggars are projected to further increase given increasingly strong appeals of urban areas to the villagers. The absence of sources of income, limited access to productive facilities, and lack of skills make begging as bread and butter. Furthermore, the tendency of laziness becomes a culture and societies’ permissive characters are enacting the activity of wandering and begging. This research applies qualitative approach with descriptive research type. The purpose of the study is to observe the social rehabilitation programs for homeless drifters and beggars with Panti Sosial Bina Karya “Pangudi Luhur” as a research location. In this study, the researcher determines to identify the inhibiting factors of the program and the consequences it’s created. By implementing the activities on food processing and tailoring, PSBK Pangudi Luhur equip their clients with work skills with an eye to prepare to improve their livelihood after rehabilitation. With the skills, the clients are expected to have capacities for entrepreneurship and employment. However, the implementations of the program are frequently hampered due to the lack of facilities and tools, the nonexistence of standard curriculum for the instructors, the difficulties in finding workplace to intern, and the low education level of the clients.